2003
DOI: 10.1002/em.10175
|View full text |Cite
|
Sign up to set email alerts
|

The comet assay: Genotoxic damage or nuclear fragmentation?

Abstract: The single cell gel electrophoresis (SCGE) or comet assay is based on the assumption that comet images result from genotoxic damage that ultimately generate DNA single- or double-strand breaks. A criticism of the assay is that some or all of the comet images may be the result of apoptosis-mediated nuclear fragmentation. The objective of this study was to determine if mutagen-induced DNA damage leading to strand breakage observed in the SCGE assay was repairable or was due to nonrepairable nuclear fragmentation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
59
0
1

Year Published

2004
2004
2010
2010

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 89 publications
(63 citation statements)
references
References 23 publications
3
59
0
1
Order By: Relevance
“…In the present study, we employed the alkaline single-cell gel electrophoresis (SCGE) assay or comet assay that quantitatively measures genomic DNA damage as singleand double-strand breaks or lesions that can be converted to strand breaks (28,29). SCGE is a sensitive genotoxicity assay and it has a high correlation in predicting carcinogens (30).…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, we employed the alkaline single-cell gel electrophoresis (SCGE) assay or comet assay that quantitatively measures genomic DNA damage as singleand double-strand breaks or lesions that can be converted to strand breaks (28,29). SCGE is a sensitive genotoxicity assay and it has a high correlation in predicting carcinogens (30).…”
Section: Introductionmentioning
confidence: 99%
“…This method is very sensitive when used under alkaline conditions and detects SSBs, DSBs, and other lesions that relax DNA (Cotelle and Ferard, 1999;Collins, 2004). To be specific to DSBs, this method should be used under a neutral pH, where the sensitivity of this method drops significantly (Rundell et al, 2003;Collins, 2004). However, several papers suggest the existence of false-positive results in apoptotic cells, potentially confounding the results of an experiment such as ours that focuses on the developmental stages of plants (Choucroun et al, 2001;Czene et al, 2002).…”
Section: Ssb and Dsb Levelsmentioning
confidence: 96%
“…It has been suggested that an efficient method for detection of strand breaks is the Comet assay (Rundell et al, 2003;Collins, 2004). This method is based on the detection of gel shifts between damaged and nondamaged DNA due to a difference in supercoiling and relies on software-based measurements of the tail length of relaxed DNA molecules (Rundell et al, 2003;Collins, 2004).…”
Section: Ssb and Dsb Levelsmentioning
confidence: 99%
See 2 more Smart Citations